2010
DOI: 10.2215/cjn.09481209
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Inpatient Hyperglycemia and Insulin Treatment after Kidney Transplantation and Future New Onset Diabetes Mellitus

Abstract: Conclusion: Development of inpatient hyperglycemia after kidney transplantation in nondiabetic patients significantly increased the risk of NODAT. Additionally, we observed a significantly increased risk of cardiovascular events in patients who developed NODAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 23 publications
(14 reference statements)
8
94
0
1
Order By: Relevance
“…Perioperative hyperglycemia is also associated with NODAT [21][22][23] . Hyperglycemia is caused by stress reaction to surgery (catecholamines), corticosteroids and restoration of renal function.…”
Section: Perioperative Hyperglycemiamentioning
confidence: 99%
See 3 more Smart Citations
“…Perioperative hyperglycemia is also associated with NODAT [21][22][23] . Hyperglycemia is caused by stress reaction to surgery (catecholamines), corticosteroids and restoration of renal function.…”
Section: Perioperative Hyperglycemiamentioning
confidence: 99%
“…In their study, Chakkera et al showed that among 377 patients who developed hyperglycemia during their transplantation hospitalization, 29% (ref. 21 ) developed NODAT within the first year after transplantation. NODAT developed in just 4% (ref.…”
Section: Perioperative Hyperglycemiamentioning
confidence: 99%
See 2 more Smart Citations
“…2,4 New-onset diabetes after transplantation (NODAT) is a common and serious disorder that curtails recipient survival. [5][6][7] NODAT is associated with cardiovascular complications [8][9][10][11] and develops in 2%-50% 12 of renal transplant recipients. Approximately 50% of recipients with NODAT require insulin therapy.…”
mentioning
confidence: 99%